Inteligência estratégica: estudo de caso em um banco público federal - Alves Junior, Oscar Marques (2016)
The herein presented research aims to identify the use of intelligence practices in the achievement of the strategic objectives in the scope of a public company of the national financial segment. For this, the study was carried out in a big federal public bank, whose implementation of the Intelligence areas are in an initial stage, which allowed the research to analyze the adherence of the Intelligence practices with the needs of the organization and the proposed models in the literature. This research was carried by means of a descriptive qualitative research, performed by a case study at Caixa Econômica Federal. By the end of the research, we were able to understand how the structures for the achievement of the studied company strategies are articulated, as well as how the relationship between the intelligence and the strategic management of the company happens. The research has demonstrated that while the process of deployment of the intelligence areas has little more than two years, the intelligence practices have already been happening in the strategic assessment of the company for more than ten years. It also notes that the investments performed in the last few years by the company in the processes of intelligence and innovation tend to boost the organization's results, especially in the improvement of processes related to its strategic management and corporative intelligence. The research, therefore, allowed the comprehension of these structures, demonstrating the existence of Intelligence practices, which inter-relate the Strategic Management of the company with the achievement of its strategic objectives.